Algebra


  1. If
    a
    +
    b
    = 1, then the value of a³ + b³ – 2 is
    ba









  1. View Hint View Answer Discuss in Forum

    a
    +
    b
    = 1
    ba

    a² + b²
    = 1
    ab

    ⇒ a² + b² = ab
    ⇒ a² – ab + b² = 0
    ∴ a³ + b³ – 2 = (a + b) (a² – ab + b²) – 2
    = – 2

    Correct Option: B

    a
    +
    b
    = 1
    ba

    a² + b²
    = 1
    ab

    ⇒ a² + b² = ab
    ⇒ a² – ab + b² = 0
    ∴ a³ + b³ – 2 = (a + b) (a² – ab + b²) – 2
    = – 2


  1. If x +
    1
    = √3, then the value ofx³ +
    1
    is :
    x









  1. View Hint View Answer Discuss in Forum

    x +
    1
    = √3
    x

    On cubing both sides,
    x + 1
    1
    ³ =( √3
    x

    ⇒ x³ +
    1
    + 3x +
    1
    = 3√3
    xx

    ⇒ x³ +
    1
    + 3√3= 3√3

    ⇒ x³ +
    1
    = 3√3= 3√3 = 0

    Correct Option: C

    x +
    1
    = √3
    x

    On cubing both sides,
    x + 1
    1
    ³ =( √3
    x

    ⇒ x³ +
    1
    + 3x +
    1
    = 3√3
    xx

    ⇒ x³ +
    1
    + 3√3= 3√3

    ⇒ x³ +
    1
    = 3√3= 3√3 = 0



  1. If a + b = 3, then the value of a³ + b³ + 9ab is :









  1. View Hint View Answer Discuss in Forum

    It is given, a + b = 3
    ∴ a³ + b³ + 9ab
    = a³ + b³ + 3ab × 3
    = a³ + b³ + 3ab (a + b)
    = (a + b)³ = (3)³ = 27

    Correct Option: A

    It is given, a + b = 3
    ∴ a³ + b³ + 9ab
    = a³ + b³ + 3ab × 3
    = a³ + b³ + 3ab (a + b)
    = (a + b)³ = (3)³ = 27


  1. If 6x² – 12x + 1 = 0, then the value of 27x³ +
    1
    is
    8x²









  1. View Hint View Answer Discuss in Forum

    6x² – 12x + 1 = 0
    Þ 6x² + 1 = 12x

    6x² + 1
    =
    12x
    2x2x

    ⇒ 3x +
    1
    = 6
    2x

    On cubing both sides,
    3x +
    1
    ³ = (6)³
    2x

    ⇒ (3x)³ +
    1
    ³ = 3 × 3x ×
    1
    3x +
    1
    = 216
    2x2x2x

    ⇒ 27x³ +
    1
    +
    9
    × 6 = 216
    8x³2

    ⇒ 27x³ +
    1
    = 216 - 27 = 189
    8x³

    Correct Option: B

    6x² – 12x + 1 = 0
    Þ 6x² + 1 = 12x

    6x² + 1
    =
    12x
    2x2x

    ⇒ 3x +
    1
    = 6
    2x

    On cubing both sides,
    3x +
    1
    ³ = (6)³
    2x

    ⇒ (3x)³ +
    1
    ³ = 3 × 3x ×
    1
    3x +
    1
    = 216
    2x2x2x

    ⇒ 27x³ +
    1
    +
    9
    × 6 = 216
    8x³2

    ⇒ 27x³ +
    1
    = 216 - 27 = 189
    8x³



  1. If x² +
    1
    = 98(x > 0), then the value ofx³ +
    1
    is
    2









  1. View Hint View Answer Discuss in Forum

    x² +
    1
    = 98

    x +
    1
    ² - 2 = 98
    x

    x +
    1
    ² = 98 + 2 = 100
    x

    ⇒ x +
    1
    = √100 = 10.......(i)
    x

    On cubing both sides,
    x +
    1
    ³ = (10)³ = 1000
    x

    ⇒ x³ +
    1
    + 3 x +
    1
    = 1000
    x

    ⇒ x³ +
    1
    + 3 × 10 = 1000

    ⇒ x³ +
    1
    = 1000 - 30 = 970

    Correct Option: A

    x² +
    1
    = 98

    x +
    1
    ² - 2 = 98
    x

    x +
    1
    ² = 98 + 2 = 100
    x

    ⇒ x +
    1
    = √100 = 10.......(i)
    x

    On cubing both sides,
    x +
    1
    ³ = (10)³ = 1000
    x

    ⇒ x³ +
    1
    + 3 x +
    1
    = 1000
    x

    ⇒ x³ +
    1
    + 3 × 10 = 1000

    ⇒ x³ +
    1
    = 1000 - 30 = 970